Photoactivated 2,3-Distyrylindoles Kill Multi-Drug Resistant Bacteria - Edwards, Leslie (Bioorg Med Chem Lett, 2018)
Compounds based on the 2,3-distyrylindole scaffold were found to exhibit bactericidal properties upon irradiation with white light. At the concentration of 1 μM, the lead compound 1 completely (ca. 10(9) CFU/mL) eradicated such Gram-positive organisms as S. aureus (MRSA, MSSA), E. faecalis (VRE), S. pyogenes and S. mutans when irradiated with white light for 2 minutes. At the concentration of 5 μM and in the presence of polymyxin E at non-bactericidal 1.25 μg/mL concentration, 1 also showed a 7-log to 9-log reductions in bacterial counts of such Gram-negative organisms as multi-drug resistant (MDR) A. baumannii, MDR P. aeruginosa, E. coli and Klebsiella pneumoniae (CRE: KPC and NDM-1), also when irradiated with white light for 2 minutes. The structure-activity relationship studies revealed that unsubstituted at benzene rings 2,3-distyrylindole 2 was most potent and gave a 5-order of magnitude eradication of a MRSA strain at the concentration of 30 nM upon irradiation with white light. Initial mechanistic experiments revealed the disruption of bacterial cell membrane, but indicated that singlet oxygen production, which is commonly associated with photodynamic therapy, may not play a role in the bactericidal effects of the 2,3-distyrylindoles.